Experimental investigation of the NOx formation and control during the self-sustaining incineration process of N-containing VOCs (DIMETHYLFORMAMIDE). (1st May 2022) - Zheng, Shijie; Qian, Yan; Wang, Xuebin; Vujanović, Milan; Zhang, Yingjia; Ur Rahman, Zia; Yang, Penghui; Duan, Fei; Tan, Houzhang; De Toni, Amir; Li, Yang; Mikulćić, Hrvoje
Highlights: The products and contents of DMF pyrolysis and fuel-lean combustion and the characteristics of SNCR for DMF combustion products were studied. The products of largest concentration in DMF pyrolysis are H2, CO, HCN and CH4 . HCN, N2 O and NO are generated as the mainly N-containing species in DMF's fuel-lean combustion, and NO concentration increases with the increase of temperature or equivalence ratio. With a lower temperature of 850 °C and high NSR ratio, SNCR has obvious effect on NO removal of the products from DMF combustion, while N2 O removal rate is low. Abstract: An experimental investigation was conducted on N, N-dimethylformamide (DMF) pyrolysis at medium-temperature followed by extremely fuel-lean combustion. Furthermore, the NH3 -SNCR (Selective non-catalytic reduction) method was studied to control NO x produced in DMF oxidation. Jet-stirred reactors (JSRs) were used in experimental investigation, because the uniform gas-phase mixing state formed by high-speed turbulence in JSR makes the validation of detailed models easier. The major gaseous species produced by pyrolysis, oxidation, and SNCR, namely H2, N2, CO, CO2, NO x, N2 O, HCN, and C x H y, are quantified because the mechanism of NO x reduction will be elaborated using these species. The results show that the main nitrogen-containing pyrolysis products are HCN and N2, taking up 65% and 25% of DMF nitrogen, while carbon-containing pyrolysis products are mostly CO, CH4 and HCN. The HCN concentration increases significantly by 42.13% as pyrolysis time increases from 1.5 to 7 s. In oxidation, HCN and N2 O concentration peaks are at 650 °C and 750 °C respectively, and NO concentration increases as temperature enhances when it is over 800 °C. A higher ratio of NO/N2 O concentration was shown in oxidation of the higher equivalence ratio. The de-NO x efficiency of NH3 -SNCR on oxidation flue gas peaked in range 825–875 °C, and as the NH3 /NO ratio increased to more than 2.5, NO removal rate tended to reach the maximum of about 50%. The N2 O removal rate rose significantly as temperature exceeded 900 °C in SNCR. The results shows the feasibility of NO emission control with DMF containing VOCs incineration in current industrial applications·NH3 -SNCR at 825–875 °C shows significant de-NO x effect, but not a proper solution to limit N2 O emission at the same time. This study could provide guidance for designing and optimizing the incinerator parameters and its de-NO x system, as well as provide validation data for future chemical kinetic model capable of predicting DMF combustion.